2013
DOI: 10.3389/fnhum.2013.00117
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical dopaminergic drug effects in extraversion: dose- and time-dependent effects of sulpiride on EEG theta activity

Abstract: Dopaminergic drugs frequently produce paradoxical effects depending on baseline performance levels, genotype, or personality traits. The present study for the first time aimed to specify the mechanisms underlying such opposite effects using the following recently reported scenario as an example: depending on the personality trait agentic extraversion (agentic facet, aE; i.e., assertiveness, dominance, ambition, positive emotionality) the selective dopamine D2 receptor antagonist sulpiride (200 mg) had opposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 104 publications
1
16
0
Order By: Relevance
“…They found that the modulatory effects of extraversion could be observed across three doses, albeit with varying time courses: introverts showed stronger sulpiride effects with smaller doses or early after administration, whereas extraverts showed sulpiride effects (opposite in direction) only for the larger doses and later after administration. Because at low blood plasma levels sulpiride is thought to primarily act on presynaptic autoreceptors and post-synaptic receptor blockade only prevails at higher blood levels, the observed pattern of opposite effects with variable time courses is consistent with stronger effects on pre-versus post-synaptic subreceptors in introverts relative to extraverts (Chavanon et al, 2013). It should also be emphasized that most of these dopamine challenge studies found that modulation of the pharmacological effects was specific to extraversion relative to other personality traits.…”
Section: Pharmacological Manipulations Of Dopaminementioning
confidence: 77%
See 2 more Smart Citations
“…They found that the modulatory effects of extraversion could be observed across three doses, albeit with varying time courses: introverts showed stronger sulpiride effects with smaller doses or early after administration, whereas extraverts showed sulpiride effects (opposite in direction) only for the larger doses and later after administration. Because at low blood plasma levels sulpiride is thought to primarily act on presynaptic autoreceptors and post-synaptic receptor blockade only prevails at higher blood levels, the observed pattern of opposite effects with variable time courses is consistent with stronger effects on pre-versus post-synaptic subreceptors in introverts relative to extraverts (Chavanon et al, 2013). It should also be emphasized that most of these dopamine challenge studies found that modulation of the pharmacological effects was specific to extraversion relative to other personality traits.…”
Section: Pharmacological Manipulations Of Dopaminementioning
confidence: 77%
“…Extraversion has also been shown to strongly modulate the effects of the selective dopamine D2 receptor antagonist sulpiride on several EEG measures including the FRN , frontal EEG asymmetry , and posterior versus frontal theta activity (Chavanon, Wacker, & Stemmler, 2013;Wacker et al, 2006) -another putative EEG index of approach motivation (Walden, Pornpattananangkul, Curlee, McAdams, & Nusslock, 2014). In each of these studies, the positive association between extraversion and the EEG measure of interest observed under placebo was not only diminished but inverted by the dopamine antagonist.…”
Section: Pharmacological Manipulations Of Dopaminementioning
confidence: 96%
See 1 more Smart Citation
“…This paradoxical effect was hypothesized to be due to prevalent blockage of presynaptic autoreceptors leading to enhanced dopamine neurotransmission (Kuroki, Meltzer, & Ichikawa, 1999). In previous studies with healthy participants, single doses of sulpiride have been well tolerated, and participants were usually not able to guess whether they received sulpiride or placebo (Chavanon, Wacker, & Stemmler, 2013;Wacker, 2018;Wacker et al 2013).…”
Section: Pharmacological Manipulationmentioning
confidence: 99%
“…Third, profiles of resting delta/theta current in the rACC have been associated with both anhedonia and blunted ventral striatal activation in response to monetary rewards, as indexed by functional magnetic resonance imaging (fMRI) (Wacker et al, 2009). Finally, pharmacological agents that affect dopaminergic activity, such as the dopamine antagonist sulpiride, which is designed to attenuate dopaminerelated activity, have been shown to modulate PFTA (Chavanon, Wacker, & Stemmler, 2013). For example, whereas unmedicated participants displayed a positive relationship between self-reported BAS sensitivity and PFTA, individuals who took a dopamine antagonist exhibited a negative relationship between BAS sensitivity and PFTA (Wacker et al, 2006).…”
Section: Approach Motivation and Posterior Versus Frontal Theta Activitymentioning
confidence: 99%